Beamwidth of beamforming vectors in millimeter-wave channels - Binjian LOU; Haiquan WANG; Yi HUANG; Ziwei LI; Yunyun YU (Dianxin kexue)
The beamforming technology is one of the core technologies in 5G and it can concentrate the transmitted energy in a specified area, thereby improving the performance of the system.But it is because of this feature that the energy is concentrated，any changes of the channel may cause to keep the receiver outside the specified area, and therefore, the performance of robustness is reduced.The concept of the beam width of a beamforming is one of the indicators to measure this tradeoff.Existing definition of beam widths are based on antennas, not on beamforming.Interms of beamforming, the definition of beam width was given and studied with the help of the concept in Grassmannian manifolds.On this basis, the method of beam width was discussed.It is found that the beam width of beamforming is closely related to the number of the transmitting antennas.The more the number of antennas, the more concentrated the energy, and the weaker robustness is.